Analisis Kejadian Bayi Lahir Berat Rendah (BBLR) pada Remaja dengan Pernikahan Usia Dini dan Faktor yang Mempengaruhinya di Kota Mataram NTB - Nurwahidah (Aspiration of Health Journal, 2024)
Marriage and childbirth at teenage age are still serious challenges faced by the Indonesian nation. The aim of this research is to analyze biological factors, economic factors and traditional factors on the incidence of Low Birth Weight Babies (LBW) among teenagers with early marriages in Mataram City. The design of this research is correlational analytic with a cross sectional approach. Data collection used a questionnaire, data analysis using the logistic regression test at α = 0.05. The results of the research show that there is an influence of early marriage on the incidence of low birth weight (LBW) babies in early married teenagers in Mataram City (p-value = 0.012 < α = 0.05). there is the influence of biological factors on the incidence of low birth weight (LBW) babies in early marriage teenagers in Mataram City (p-value = 0.038 < α = 0.05), there is the influence of economic factors on the incidence of low birth weight babies (LBW) in teenagers early marriage in Mataram City (p-value = 0.025 < α = 0.05), there is no influence of traditional factors on the incidence of Low Birth Weight (LBW) Babies in early marriage teenagers in Mataram City (p-value = 0.740 > α = 0.05). The influence of the independent variables together on the incidence of LBW is obtained by p-value = 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, which means that there is a joint influence between early marriage, biological factors, economic factors and traditional factors on the event. Low Birth Weight (LBW) Babies in Mataram City.